Konsep Khāfī Dilalāh Perspektif Ulama Salaf dan Khalaf - Ainun Mardiah, Nur; Hilal, Fatmawati; Sanusi, Nur Taufiq (Jurnal ini dipublikasikan oleh Pusat Penelitian dan Pengabdian Publikasi (P3M) STAI Nahdlatul Watan Samawa-licensed under a Creative Commons Attribution-ShareAlike 4.0 International License., 2025)
This research analyzes the concept of Khāfī Dilalāh an ambiguous legal term due to external factors from the perspectives of Salaf and Khalaf scholars, using the term al-sāriq from Q.S. al-Maidah verse 38 as a case study, with implications on some similar issues. Employing a qualitative-comparative methodology via library research, this study aims to examine how the differing approaches to istinbat the Salaf's textualism versus the Khalaf's rational-contextualism impact legal outcomes. The findings reveal that Salaf scholars tend to limit the application of law to explicit texts, whereas Khalaf scholars expand it based on the underlying ‘illat (legal reason) and Maqāsid al-Shari'ah (objectives of Islamic law). This divergence is evident in the resolution of corruption cases, which are consensually categorized as jarīmah ta'zir rather than hadd. The study concludes that this methodological difference is not merely theoretical but has direct causal implications for legal application and the relevance of contemporary Islamic jurisprudence, thereby addressing a fundamental gap in existing literature.